PERSEPSI PEMAKAI LAPORAN KEUANGAN PEMERINTAH DAERAH TERHADAP INDEPENDENSI AUDITOR BADAN PEMERIKSA KEUANGAN - Suhardi Suhardi (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2012)
This research examines the perception of financial statement user of local government to state audit board (BPK) of auditor independence. With confirmation seven independence determinants a) the duration assignation of audit, b) independence in budget audit, c) the limited assignation time and resources provided by for auditor BPK, d) existence of family relationship, e) existence of tendency to side, because political confidence or social, f) Access to information without resistance, g) freedom to determine matter and time reports and freedom to publish and dissemination of inspection reports. The sampling technique applied is purposive sampling and research data is primary data collected from users of financial statement of local government that is local government officer, member of Local Parliament (DPRD), Academician, and public users in Jogjakarta. Examination of hypothesis done by using proportion test, chi square and Analysis of Variance (ANOVA). Result of research indicates that in general financial statement users of local government assumes auditor BPK has not independent in executing inspection, seven independence determinants in general will have an effects or can destroy independence of auditor BPK, although some group have differs in opinion to some factors Keywords: Perception, Independence, Local Government Financial Statements, State Audit Board